Problems of legal regulation of intercultural competence of a teacher on the example of legal education (Journal of actual problems of jurisprudence, 2022)
The number of international students is one of the indicators of the international effectiveness of universities. That is why we are working to improve the intercultural competence of teachers and staff of Kazakhstani universities who work (or will work) with foreign students. The insufficient level of the teachers' ICC complicates the educational process, levels the opportunity to take advantage of the intercultural environment for learning, can lead to a deterioration of group interaction and, as a result, to a decrease in the prestige of education in the eyes of foreign students. The focus on the development of a scientific and methodological base for the expansion of the teachers' MCC, thus, confirms the compliance of our project with the growing need to train teachers of the Kazakh higher school to work with a multilingual (and multicultural) audience of foreign students.The aim of the research is to develop a conceptual, legal and methodological framework for building a sustainable model for expanding the intercultural competence (ICC) of teaching lawyers, with the aim of introducing and improving the ICC for training lawyers-teachers of Kazakhstan higher school to work with a multilingual (and multicultural) audience represented by foreign students. The results of the research will contribute to building more effective models for solving new socio-pedagogical and educational tasks that the expansion of international academic contacts brings, which in the long term will serve to strengthen the competitiveness of higher education in the Republic of Kazakhstan.The article is based on the materials of a scientific project on the topic: Intercultural competence of a university teacher and its impact on improving the competitiveness of higher education in Kazakhstan.Keywords: the right to education, legal education, foreign and exchange students, competitiveness of Kazakhstan’s education, intercultural communicative competence